The Effectiveness Of Using Picture Series On Students’ English Writing Skill Of Recount Text At SMA Dharma Bakti Medan - Roilentina Sihotang, Zulfitri (ALACRITY : Journal of Education, 2022)
This research consist to determine the effectiveness of using picture series on students' writing skills in recount texts at SMA Dharma bakti Medan. The design of this research is experimental research. They consist of 150 students and the sample consists of 40 students then divided into two class; The experimental class of 20 students (X-IPA) was taught using serial pictures while the control class of 20 students (X-IPS) was taught without serial pictures. The research instrument used a written test, The test is to make a story text analyzing the general structure of the story text. the score of a text can be obtained from the general structure and grammatical arrangement of the text. After applying the test to the students, the writer analyzes the data using the t-test formula which is commonly used. after calculating and analyzing the data, it was concluded that the was higher than the (4.47> 1.70). it shows that there is a significant difference. The experimental pre-test score was 39 and the post-test score was 60.25, the difference was -21.25. The value of is greater than (4.47>1.70) df is 38, and the level of significance is 0.05. it is stated that the effectiveness of the use of picture series has a significant influence on students' ability to write story texts, Based on the test results above, it shows that picture series can improve students' writing skills in writing story texts. it can be concluded that this research hypothesis is accepted.